Theta Functions - 20.6 Power Series

From testwiki
Revision as of 17:35, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
20.6.E3 θ 2 ( π z | τ ) = θ 2 ( 0 | τ ) exp ( - j = 1 1 2 j α 2 j ( τ ) z 2 j ) Jacobi-theta-tau 2 𝜋 𝑧 𝜏 Jacobi-theta-tau 2 0 𝜏 superscript subscript 𝑗 1 1 2 𝑗 subscript 𝛼 2 𝑗 𝜏 superscript 𝑧 2 𝑗 {\displaystyle{\displaystyle\theta_{2}\left(\pi z\middle|\tau\right)=\theta_{2% }\left(0\middle|\tau\right)\exp\left(-\sum_{j=1}^{\infty}\frac{1}{2j}\alpha_{2% j}(\tau)z^{2j}\right)}}
\Jacobithetatau{2}@{\pi z}{\tau} = \Jacobithetatau{2}@{0}{\tau}\exp@{-\sum_{j=1}^{\infty}\frac{1}{2j}\alpha_{2j}(\tau)z^{2j}}

JacobiTheta2(Pi*z,exp(I*Pi*tau)) = JacobiTheta2(0,exp(I*Pi*tau))*exp(- sum((1)/(2*j)*(sum(sum((m -(1)/(2)+ n*tau)^(- 2*j), m = - infinity..infinity), n = - infinity..infinity))*(z)^(2*j), j = 1..infinity))
EllipticTheta[2, Pi*z, Exp[I*Pi*(\[Tau])]] == EllipticTheta[2, 0, Exp[I*Pi*(\[Tau])]]*Exp[- Sum[Divide[1,2*j]*(Sum[Sum[(m -Divide[1,2]+ n*\[Tau])^(- 2*j), {m, - Infinity, Infinity}, GenerateConditions->None], {n, - Infinity, Infinity}, GenerateConditions->None])*(z)^(2*j), {j, 1, Infinity}, GenerateConditions->None]]
Aborted Aborted Skipped - Because timed out Skipped - Because timed out
20.6.E4 θ 3 ( π z | τ ) = θ 3 ( 0 | τ ) exp ( - j = 1 1 2 j β 2 j ( τ ) z 2 j ) Jacobi-theta-tau 3 𝜋 𝑧 𝜏 Jacobi-theta-tau 3 0 𝜏 superscript subscript 𝑗 1 1 2 𝑗 subscript 𝛽 2 𝑗 𝜏 superscript 𝑧 2 𝑗 {\displaystyle{\displaystyle\theta_{3}\left(\pi z\middle|\tau\right)=\theta_{3% }\left(0\middle|\tau\right)\exp\left(-\sum_{j=1}^{\infty}\frac{1}{2j}\beta_{2j% }(\tau)z^{2j}\right)}}
\Jacobithetatau{3}@{\pi z}{\tau} = \Jacobithetatau{3}@{0}{\tau}\exp@{-\sum_{j=1}^{\infty}\frac{1}{2j}\beta_{2j}(\tau)z^{2j}}

JacobiTheta3(Pi*z,exp(I*Pi*tau)) = JacobiTheta3(0,exp(I*Pi*tau))*exp(- sum((1)/(2*j)*(sum(sum((m -(1)/(2)+(n -(1)/(2))*tau)^(- 2*j), m = - infinity..infinity), n = - infinity..infinity))*(z)^(2*j), j = 1..infinity))
EllipticTheta[3, Pi*z, Exp[I*Pi*(\[Tau])]] == EllipticTheta[3, 0, Exp[I*Pi*(\[Tau])]]*Exp[- Sum[Divide[1,2*j]*(Sum[Sum[(m -Divide[1,2]+(n -Divide[1,2])*\[Tau])^(- 2*j), {m, - Infinity, Infinity}, GenerateConditions->None], {n, - Infinity, Infinity}, GenerateConditions->None])*(z)^(2*j), {j, 1, Infinity}, GenerateConditions->None]]
Aborted Aborted Skipped - Because timed out Skipped - Because timed out
20.6.E5 θ 4 ( π z | τ ) = θ 4 ( 0 | τ ) exp ( - j = 1 1 2 j γ 2 j ( τ ) z 2 j ) Jacobi-theta-tau 4 𝜋 𝑧 𝜏 Jacobi-theta-tau 4 0 𝜏 superscript subscript 𝑗 1 1 2 𝑗 subscript 𝛾 2 𝑗 𝜏 superscript 𝑧 2 𝑗 {\displaystyle{\displaystyle\theta_{4}\left(\pi z\middle|\tau\right)=\theta_{4% }\left(0\middle|\tau\right)\exp\left(-\sum_{j=1}^{\infty}\frac{1}{2j}\gamma_{2% j}(\tau)z^{2j}\right)}}
\Jacobithetatau{4}@{\pi z}{\tau} = \Jacobithetatau{4}@{0}{\tau}\exp@{-\sum_{j=1}^{\infty}\frac{1}{2j}\gamma_{2j}(\tau)z^{2j}}

JacobiTheta4(Pi*z,exp(I*Pi*tau)) = JacobiTheta4(0,exp(I*Pi*tau))*exp(- sum((1)/(2*j)*(sum(sum((m +(n -(1)/(2))*tau)^(- 2*j), m = - infinity..infinity), n = - infinity..infinity))*(z)^(2*j), j = 1..infinity))
EllipticTheta[4, Pi*z, Exp[I*Pi*(\[Tau])]] == EllipticTheta[4, 0, Exp[I*Pi*(\[Tau])]]*Exp[- Sum[Divide[1,2*j]*(Sum[Sum[(m +(n -Divide[1,2])*\[Tau])^(- 2*j), {m, - Infinity, Infinity}, GenerateConditions->None], {n, - Infinity, Infinity}, GenerateConditions->None])*(z)^(2*j), {j, 1, Infinity}, GenerateConditions->None]]
Aborted Aborted Skipped - Because timed out Skipped - Because timed out
20.6#Ex2 β 2 j ( τ ) = 2 2 j γ 2 j ( 2 τ ) - γ 2 j ( τ ) subscript 𝛽 2 𝑗 𝜏 superscript 2 2 𝑗 subscript 𝛾 2 𝑗 2 𝜏 subscript 𝛾 2 𝑗 𝜏 {\displaystyle{\displaystyle\beta_{2j}(\tau)=2^{2j}\gamma_{2j}(2\tau)-\gamma_{% 2j}(\tau)}}
\beta_{2j}(\tau) = 2^{2j}\gamma_{2j}(2\tau)-\gamma_{2j}(\tau)

(sum(sum((m -(1)/(2)+(n -(1)/(2))*tau)^(- 2*j), m = - infinity..infinity), n = - infinity..infinity)) = (2)^(2*j)* gamma[2*j](2*tau)-(sum(sum((m +(n -(1)/(2))*tau)^(- 2*j), m = - infinity..infinity), n = - infinity..infinity))
(Sum[Sum[(m -Divide[1,2]+(n -Divide[1,2])*\[Tau])^(- 2*j), {m, - Infinity, Infinity}, GenerateConditions->None], {n, - Infinity, Infinity}, GenerateConditions->None]) == (2)^(2*j)* Subscript[\[Gamma], 2*j][2*\[Tau]]-(Sum[Sum[(m +(n -Divide[1,2])*\[Tau])^(- 2*j), {m, - Infinity, Infinity}, GenerateConditions->None], {n, - Infinity, Infinity}, GenerateConditions->None])
Skipped - no semantic math Skipped - no semantic math - -